(untitled) (Research, Society and Development, 2021)
The reflexes caused by COVID-19, caused a great anxiety for the mass and its rulers, since its propagation is fast and lethal. In this context, an accurate and safe treatment to reduce probable complications, which can minimize the morbidity and mortality resulting from the disease. This study aims to highlight the existing scientific evidence of increased sales in the use of the following drugs: azithromycin 500 mg, hydroxychloroquine, zinc, vitamin C, ivermectin and acetylcysteine 600 mg, in a private drugstore in the city of Redenção-Pará. The study was supported by a quantitative and qualitative research, during the period from January 2019 to December 2020. There were 2,787 sales of the analyzed drugs, where ivermectin was the most sold drug, mainly in the months of June and July 2020; followed by vitamin C, dexamethasone, dipyrone and anticoagulant. The use of these medications without the prescription of a trained professional can cause serious damage to health, even leading to death.